2010
DOI: 10.1016/j.jtcvs.2009.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Factors favoring stent-graft collapse after thoracic endovascular aortic repair

Abstract: This stent-graft-related complication seems related to poor apposition of the stent grafts in the highly angulated aortic arch. Excessive stent-graft oversizing could be an additional causative factor. Accurate assessment of aortic arch anatomic features, as well as the choice and sizing of the device, may prevent this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 21 publications
0
79
0
1
Order By: Relevance
“…Les facteurs favorisant cet effondrement sont le surdimensionnement de l'endoproth ese et la mauvaise apposition dans une arche aortique fortement angul e. Le traitement de cette complication consiste la plupart du temps en une r eparation endovasculaire en ajoutant une prolongation proximale de l'endoproth ese. [23][24][25] Un autre probl eme li e au TEVAR est la couverture potentielle de l'ASCG. Un examen des publications de la litt erature montre principalement deux tendances.…”
Section: Discussionunclassified
“…Les facteurs favorisant cet effondrement sont le surdimensionnement de l'endoproth ese et la mauvaise apposition dans une arche aortique fortement angul e. Le traitement de cette complication consiste la plupart du temps en une r eparation endovasculaire en ajoutant une prolongation proximale de l'endoproth ese. [23][24][25] Un autre probl eme li e au TEVAR est la couverture potentielle de l'ASCG. Un examen des publications de la litt erature montre principalement deux tendances.…”
Section: Discussionunclassified
“…The "bird beak configuration [9] [10] is a radiological finding of a wedge shaped gap between the undersurface of the SG and the aortic wall occurred in the SG at the lesser curvature of the ascending aorta was absent and no leakage was observed in the SG. Further, intimal hyperplasia was observed to occupy the majority of endoluminal SG.…”
Section: Case Reportmentioning
confidence: 99%
“…This may ultimately induce to premature device failure and endograft collapse/ infolding, which usually requires a secondary intervention by means of re-do TEVAR or conversion to open surgery with attendant high morbidity and mortality [7][8][9][10]. The incidence rates of endograft collapse after TEVAR for traumatic injuries are not well defined [8,11], although collapses usually present in the early post-operative period (median time of 15 days) [12]. It has been recently reported that the Gore TAG thoracic endoprosthesis (W. L. Gore and Assoc, Flagstaff, Ariz) accumulated a 0.4% frequency rate of device collapse among 33,000 endografts distributed worldwide [6].…”
Section: Introductionmentioning
confidence: 99%
“…Endograft infolding-related mortality rates of 16.9% for asymptomatic patients and 27.3% for symptomatic patients within 3 years of diagnosis [11,13,14]. Collapses are most often observed when the proximal extent of the endograft is in the transverse arch with malapposition of the endograft wall along the lesser curvature of the aorta (the so-called "bird-beak" phenomenon) [9][10][11]14]. Bird-beaking is not desirable because it exposes the graft undersurface to the force of the bloodstream.…”
Section: Introductionmentioning
confidence: 99%